(untitled) (International Journal of Physiotherapy, 2016)
Background: Healthy individuals, to ease and accomplish their activities of daily living they need flexible body without any tightness in the muscles, particularly those used for a definite function. Cooling soft tissues in a lengthened position after stretching has been shown to promote more lasting increases in soft tissue length and minimize post stretch muscle soreness. There are less documented studies which compared modified proprioceptive neuromuscular facilitation (PNF) stretch over passive manual stretch with cold application commonly after the interventions. Methods: Thirty high school going healthy students were divided into two groups- Group I received Passive Manual stretching (n=15) and Group II received modified PNF stretching (n=15) and both groups received cold application after the interventions for 10 minutes commonly for 5 days. ROM was taken on day 1, day 5 and day 7. Results: After day 7, Group II with Modified PNF stretching along with cold application showed a significant increase in range of motion tested with active knee extension test (AKET). Conclusion: Modified PNF stretching is considered to be the effective intervention in increasing and maintaining ROM in AKET over passive manual stretching with cold applications commonly after the interventions.